Military Sciences: a space for articulating the phenomenon of war and professional experience - Silva, Marco Aurélio Vasques (2025)
This is a reflection on the importance of professional experience for the deepening of the study of Military Sciences, in a context of the analysis of the phenomenon of War. With a qualitative bias, a deductive perspective was adopted, based on bibliographic research, with the support of content analysis. Since war is a concrete social phenomenon, which is expressed on the battlefield, the perspective that Military Sciences are close to Applied Social Sciences is corroborated. Thus, it is suggested that experience, resulting from professional practice, provides elements of reflection that contribute analytically to the study of War and, consequently, to the improvement of Military Sciences. In this context, the need to structure a coherent methodology for conducting analyses and observations is highlighted, in order to avoid subjectivity and personalism, as well as to report the gain in the quality of analyses with the increase of experience as a substantive factor in the process of studying War and Military Sciences.